A brominated flame retardant reinforced nylon material and preparation method thereof

By using zirconium hydroxide and hydrotalcite as composite adsorbents in bromine flame retardant nylon materials and combining glass fibers, the problem of acid corrosive gas is solved, the stability and high-temperature aging resistance of the material are improved, and it is suitable for high-temperature environments. electronic and electrical products.

CN116376274BActive Publication Date: 2024-12-17KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202310412742.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2024-12-17
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

Bromine flame retardants are prone to decomposition and produce acidic corrosive gases during processing or high-temperature aging, resulting in a decrease in the material's aging resistance. The existing physical adsorbents have limited effects and may re-release gases in high-temperature environments, affecting product performance.

Method used

Zirconium hydroxide and hydrotalcite are used as composite adsorbents to adsorb and neutralize acid corrosive gases through physical anchoring and chemical neutralization reactions, improve the stability and high-temperature aging resistance of the material, and enhance the tensile strength by introducing glass fibers. .

Benefits of technology

It significantly improves the stability and high-temperature aging resistance of bromine flame-retardant nylon materials, maintains the flame-retardant and mechanical properties of the products, and is suitable for electronic and electrical products under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004183782860000051
    Figure BDA0004183782860000051
  • Figure BDA0004183782860000061
    Figure BDA0004183782860000061
  • Figure BDA0004183782860000062
    Figure BDA0004183782860000062
Patent Text Reader

Abstract

The present invention discloses a bromine-based flame-retardant reinforced nylon material and a preparation method thereof, and belongs to the technical field of engineering plastics. The bromine-based flame-retardant reinforced nylon material of the present invention is compounded with specific zirconium hydroxide and hydrotalcite to solve the problem of acidic corrosive gas from both physical and chemical aspects, improve the stability of the bromine-based flame-retardant nylon resin system, and enable the product to have good high temperature aging resistance. The present invention also discloses a preparation method of the product and its application in the preparation of electronic and electrical products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastics, and in particular to a bromine-based flame-retardant reinforced nylon material and a preparation method thereof. Background Art

[0002] Flame-retardant nylon materials are widely used due to their good mechanical properties and thermal stability. Among them, the flame-retardant nylon of the brominated flame retardant system has the characteristics of high flame retardant efficiency and wide application range. However, brominated flame retardants are prone to decomposition during processing or high-temperature aging to produce acidic corrosive gases such as hydrogen bromide, which weakens the aging resistance of the material. In order to solve this problem, some physical adsorbents are often introduced into the product to absorb acidic corrosive gases in the prior art. However, the adsorption effect of this component is limited, and it is difficult to achieve long-term effect under high temperature environment. At the same time, when the product is affected by external factors, these physical adsorbents may re-release acidic gases, causing the performance of the product to decline faster. On the other hand, some commonly used physical adsorbents will cause the resin crystallinity of the product to decrease after being introduced into the nylon material system, so that the mechanical properties and high temperature aging resistance of the product are affected. Summary of the invention

[0003] Based on the defects of the prior art, the purpose of the present invention is to provide a brominated flame retardant reinforced nylon material, which is compounded with specific zirconium hydroxide and hydrotalcite to solve the problem of acidic corrosive gas from both physical and chemical aspects, improve the stability of the brominated flame retardant nylon resin system and enable the product to have good high temperature aging resistance.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] A brominated flame-retardant reinforced nylon material comprises the following components in parts by weight:

[0006] 20-50 parts of nylon resin, 18-25 parts of brominated flame retardant, 9-12 parts of antimony flame retardant, 10-50 parts of glass fiber, 0.3-0.5 parts of composite adsorbent and 0.4-3 parts of processing aid;

[0007] The composite adsorbent comprises zirconium hydroxide and hydrotalcite, and the mass ratio of the two is (1:1) to (4:1).

[0008] In the brominated flame retardant reinforced nylon material system of the present invention, the brominated flame retardant is prone to produce acidic hydrogen bromide and other smoke-type substances when heated or burned. This substance is corrosive to both nylon resin and processing aids, which seriously affects the stability of the product itself, especially the high temperature aging resistance. Therefore, the inventor uses zirconium hydroxide and hydrotalcite as a composite adsorbent to deal with this problem: zirconium hydroxide is a natural porous amphoteric material. When encountering acidic gas substances produced by brominated flame retardants, it can not only quickly physically anchor and adsorb the substance through a porous structure, but also directly react with the substance to neutralize, but the excessive introduction of zirconium hydroxide will cause the product's high temperature aging resistance to decrease; hydrotalcite is a layered double metal hydroxide, which has interlayer ion exchangeability and alkalinity, and can be coordinated with zirconium hydroxide to achieve chemical inhibition of acidic corrosive gases. The most important thing is that it has good thermal stability. After being matched with zirconium hydroxide, the stability of the prepared brominated reinforced nylon material is improved, and the product has excellent high temperature aging resistance.

[0009] The introduction of glass fiber can improve the tensile strength of the product. Under the premise of not affecting the flame retardancy and high temperature aging resistance of the product, technicians in this field can add appropriate glass fiber as a functional filler to the product components according to actual conditions.

[0010] More preferably, the average pore diameter of the zirconium hydroxide is 1.5 to 3 nm.

[0011] The test method for the average pore size of the zirconium hydroxide is: placing the product in a muffle furnace at 750° C. for 1 hour, placing the residual ash in a scanning electron microscope to observe and confirm, measure, and count the average pore size of the zirconium hydroxide.

[0012] The size of the pore size in zirconium hydroxide is related to its anchoring ability for acidic corrosive gas substances, and also affects its dispersion stability in the product, so it cannot be too large or too small. After testing and screening, zirconium hydroxide with a pore size within the above range has the best matching performance. At the same time, the zirconium hydroxide of the present invention can be purchased from the market according to actual conditions, or it can be made by itself according to the teachings of the existing disclosed preparation scheme.

[0013] Preferably, the particle size D50 of the zirconium hydroxide is 20-40 μm, and the particle size D50 of the hydrotalcite is 0.4-0.7 μm.

[0014] Preferably, the nylon resin is at least one of PA6 and PA66.

[0015] It should be noted that, in the present invention, the content of the nylon resin in the brominated flame-retardant reinforced nylon material is not less than 20 wt %, and the additive amount meets the raw material and production requirements of conventional nylon composite materials.

[0016] Preferably, the brominated flame retardant is at least one of decabromodiphenylethane, brominated polystyrene and brominated ethylene oxide.

[0017] Preferably, the antimony-based flame retardant is antimony trioxide.

[0018] Preferably, the processing aid is at least one of an antioxidant and a lubricant.

[0019] More preferably, the antioxidant is at least one of a hindered phenol antioxidant, a hindered amine antioxidant, and a phosphite antioxidant.

[0020] More preferably, the lubricant is at least one of an organic silicone lubricant, a stearate lubricant, an amide lubricant, and a fatty ester lubricant.

[0021] Another object of the present invention is to provide a method for preparing the brominated flame retardant reinforced nylon material, comprising the following steps:

[0022] The components except glass fiber are placed in a high-speed mixer for mixing according to proportion, and then transferred from the main feeding port to a twin-screw extruder. At the same time, glass fiber is added to the side feeding port for mixing and melt extrusion granulation to obtain the brominated flame retardant reinforced nylon material.

[0023] The preparation method of the brominated flame-retardant reinforced nylon material of the present invention has simple operation steps and can realize industrial large-scale production.

[0024] Preferably, the setting temperature of the twin-screw extruder during the melt extrusion granulation is: 200-270°C.

[0025] Another object of the present invention is to provide the use of the brominated flame retardant reinforced nylon material in the preparation of electronic and electrical products.

[0026] The brominated flame-retardant reinforced nylon of the present invention can adjust the filler and flame retardant components according to actual conditions to adapt to the mechanical requirements and flame retardant performance requirements required by various usage scenarios. The most important thing is that it effectively solves the problem of decreased high-temperature aging resistance of products caused by high-temperature decomposition of brominated flame retardants while ensuring the high flame retardancy efficiency of brominated flame retardant components. After testing, the tensile strength retention rate of the product can reach 50% or more after being subjected to a high temperature of 200°C for 504 hours, and the retention rate can reach more than 65% after being subjected to a high temperature of 168 hours. It is very suitable for the field of electronic and electrical products with high requirements for high-temperature aging resistance and flame retardancy.

[0027] The beneficial effect of the present invention is that the present invention provides a brominated flame-retardant reinforced nylon material, which is compounded with specific zirconium hydroxide and hydrotalcite to solve the problem of acidic corrosive gas from both physical and chemical aspects, improve the stability of the brominated flame-retardant nylon resin system, and make the product have good high temperature aging resistance. The present invention also provides a preparation method of the product and its application in the preparation of electronic and electrical products. DETAILED DESCRIPTION

[0028] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0029] Examples 1 to 8

[0030] The embodiments of the brominated flame retardant reinforced nylon material and the preparation method thereof of the present invention, the components of the brominated flame retardant reinforced nylon material are shown in Table 1.

[0031] The preparation method of the brominated flame retardant reinforced nylon material comprises the following steps:

[0032] The components except glass fiber are placed in a high-speed mixer for mixing according to proportion, and then transferred from the main feeding port to a twin-screw extruder. At the same time, glass fiber is added to the side feeding port for mixing and melt extrusion granulation to obtain the brominated flame retardant reinforced nylon material.

[0033] The temperature of the twin-screw extruder is set at 200-270°C.

[0034] Comparative Examples 1 to 9

[0035] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.

[0036] Among the components described in each embodiment and comparative example,

[0037] Nylon resin 1PA66 EP158 is PA66 produced by Huafeng Group Co., Ltd.;

[0038] Nylon resin 2PA6 HY2800A is PA6 produced by Haiyang Chemical Fiber;

[0039] Brominated flame retardant 1 is brominated polystyrene produced by Albemarle, USA;

[0040] Brominated flame retardant 2 is decabromodiphenylethane produced by Albemarle, USA;

[0041] The antimony flame retardant is commercially available antimony trioxide;

[0042] The glass fiber is 584 produced by China Jushi Co., Ltd.;

[0043] Antioxidant 1 is a commercially available hindered amine antioxidant;

[0044] Antioxidant 2 is a commercially available phosphite antioxidant;

[0045] The lubricant is a commercially available organic silicone lubricant;

[0046] Zirconium hydroxide 1 was produced by Jiangxi Jingan High-Tech Co., Ltd., with an average pore size of 2.65 nm and a particle size D50 of 34.2 μm;

[0047] Zirconium hydroxide 2 was produced by Jiangxi Jingan High-Tech Co., Ltd., with an average pore size of 2.0 nm and a particle size D50 of 22.6 μm;

[0048] Zirconium hydroxide 3 was produced by Jiangxi Jingan High-Tech Co., Ltd., with an average pore size of 7.83 nm and a particle size D50 of 38.6 μm;

[0049] Zirconium hydroxide 4 was produced by Jiangxi Jingan High-Tech Co., Ltd., with a pore size too small to be detected (i.e., pores of 2 nm or less), and a particle size D50 of 88 nm;

[0050] The hydrotalcite was DHT-4A produced by Kyowa Chemical of Japan, with a particle size D50 of 0.5 μm;

[0051] Compound ingredient 1 is ultrafine talcum powder produced by Liaoning Aihai Yimi Mining, with a pore size too small to be detected (i.e., pores of 2 nm or less), and a particle size D50 of 0.65 μm;

[0052] Compound 2 is kaolin produced by China Kaolin Co., Ltd., with an average pore size that is too small to be detected (i.e., pores of 2 nm or less), and a particle size D50 of 1 μm;

[0053] Aluminum hydroxide is commercially available aluminum hydroxide with an average pore size of 3.0 nm and a particle size D50 of 23 μm;

[0054] Compound ingredient 3 is diatomaceous earth produced by Linjiang Yiruishi, with an average pore size of 8 nm and a particle size D50 of 16 μm.

[0055] Unless otherwise specified, the component raw materials used in each embodiment and comparative example of the present invention are all commercially available raw materials, and the component raw materials used in each parallel experiment are all of the same kind. The zirconium hydroxides 1 to 4 described in the present invention are all products of different specifications prepared by the same manufacturer, and those skilled in the art can also refer to the relevant patent technology of the manufacturer (such as CN105502490A) or other existing preparation technologies of zirconium hydroxides (such as CN101389570A) to obtain them by themselves. At the same time, it should be noted that after the zirconium hydroxides 1 to 4 and hydrotalcite used in the present invention and the composite materials 1 to 3 grade aluminum hydroxide used in the comparative example are processed and prepared, the obtained nylon material is calcined, and the corresponding raw materials are screened and EDS confirmed and size statistics are performed on the scanning electron microscope, and a sample is determined by three statistical averages in a parallel experiment. It is found that the average pore size of each raw material before and after the product preparation is ≤5%, so it can be regarded as the pore size of the product before and after preparation. There is almost no change.

[0056] Table 1

[0057] Component weight Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Nylon resin 1 50 30 30 30 30 30 30 Nylon resin 2 20 10 10 10 10 10 10 Brominated flame retardant 1 25 20 20 20 20 20 20 Brominated flame retardant 2 18 Antimony flame retardant 12 9 10 10 10 10 10 10 Fiberglass 10 50 30 30 30 30 30 30 Antioxidant 1 0.8 0.5 0.6 0.6 0.6 0.6 0.6 0.6 Antioxidant 2 0.4 0.3 0.4 0.4 0.4 0.4 0.4 0.4 Lubricants 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 Zirconium Hydroxide 1 0.3 0.2 0.3 0.2 0.32 Zirconium Hydroxide 2 0.3 Zirconium Hydroxide 3 0.3 Zirconium Hydroxide 4 0.3 Hydrotalcite 0.2 0.1 0.1 0.2 0.08 0.1 0.1 0.1

[0058] Table 2

[0059]

[0060]

[0061] Effect Example 1

[0062] In order to verify the performance of the brominated flame retardant reinforced nylon material of the present invention, the tensile strength test and high temperature aging resistance test were performed on the products of each embodiment and comparative example. The specific steps are as follows:

[0063] The samples of each embodiment were injection molded into 3 mm thick tensile specimens according to the standard of ISO 527-2-2012 Type 1BA. According to the UL ASTM 746B-2018 standard, the specimens were first placed in an oven at 170°C for 48 hours and then tested for the initial tensile strength of the samples at a tensile speed of 10 mm / min. Subsequently, each specimen was placed in an oven at 200°C for 3 weeks of aging test and the tensile strength of the specimens after high temperature treatment was tested by the same test method at 168 hours, 336 hours and 504 hours of aging, and finally the tensile strength retention rate was calculated. The test results are shown in Tables 3 and 4.

[0064] Table 3

[0065]

[0066] Table 4

[0067]

[0068] As can be seen from Table 1, compared with Comparative Examples 1 and 2, the initial tensile strength of the products of Examples 1 and 2 is almost the same, indicating that the introduction of the composite adsorbent in the brominated flame retardant reinforced nylon material component of the present invention does not cause changes in the tensile strength of the product, and after 200 ° C high temperature treatment for 504h, the product has a significantly improved tensile strength retention rate compared to the products of Comparative Examples 1 and 2, and the product has excellent high temperature aging resistance. For different types of nylon and different types of brominated flame retardants, the composite adsorbent in the product of the present invention has good performance, can effectively reduce the negative impact of the thermal decomposition product of brominated flame retardants, and can improve the crystallinity of the product. When the particle size and pore size of the selected zirconium hydroxide raw material are different (after processing, the pore size of zirconium hydroxide does not change much), the dispersion of the product after preparation and the anchoring efficiency of acidic corrosive gas substances are also different, so when the pore size of zirconium hydroxide in the product is maintained at 1.5-3μm, the particle size D50 is 20-40μm, and the comprehensive performance of the product is the best. From the comparison between the products of Examples 3 to 5 and Comparative Examples 1 to 4, it can be seen that in the composite adsorbent component of the product, zirconium hydroxide and hydrotalcite have the effect of synergistically adsorbing and reacting acidic corrosive gas substances and improving the crystallinity of the product, but when the proportion of zirconium hydroxide or hydrotalcite is too high, the performance retention rate of the product will deteriorate, and may even be worse than the product of Comparative Example 1 or 2. From the performance comparison between the products of Example 3 and Comparative Examples 5 to 8, it can be seen that the composite combination of zirconium hydroxide and hydrotalcite is specific in the system of the product of the present invention. Replacing zirconium hydroxide or hydrotalcite with other common existing adsorbents (reactants) cannot achieve the same technical effect, but will weaken the performance of the product.

[0069] Further, the products of Examples 1 to 3 and the products of Comparative Examples 1 to 2 were subjected to flame retardancy tests, and the specific steps were as follows: a vertical combustion performance test was conducted according to GB / T 2408-2008 standard, the thickness of the test specimen was 0.8 mm, and the flame retardancy levels were V-0, V-1, V-2, and no level. In the test results, the flame retardancy levels of the five samples were all V-0, which fully demonstrated that the composite adsorbent in the brominated flame retardant reinforced nylon material of the present invention not only did not affect the tensile properties of the product, but also did not affect the high-efficiency flame retardancy of the brominated flame retardant itself.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A brominated flame retardant reinforced nylon material, characterized in that: The composition comprises the following components in parts by weight: 20-50 parts of nylon resin, 18-25 parts of brominated flame retardant, 9-12 parts of antimony flame retardant, 10-50 parts of glass fiber, 0.3-0.5 parts of composite adsorbent and 0.4-3 parts of processing aid; The composite adsorbent comprises zirconium hydroxide and hydrotalcite, and the mass ratio of the two is (1:1) to (4:1); the average pore diameter of the zirconium hydroxide is 1.5 to 3 nm, and the particle diameter D50 is 20 to 40 μm.

2. The brominated flame retardant reinforced nylon material according to claim 1, characterized in that: The particle size D50 of the hydrotalcite is 0.4-0.7 μm.

3. The brominated flame retardant reinforced nylon material according to claim 1, characterized in that: Include at least one of the following (1) to (4): (1) The nylon resin is at least one of PA6 and PA66; (2) The brominated flame retardant is at least one of decabromodiphenylethane, brominated polystyrene, and brominated ethylene oxide; (3) The antimony-based flame retardant is antimony trioxide; (4) The processing aid is at least one of an antioxidant and a lubricant.

4. The brominated flame retardant reinforced nylon material according to claim 3, characterized in that: The antioxidant is at least one of a hindered phenol antioxidant, a hindered amine antioxidant, and a phosphite antioxidant; The lubricant is at least one of an organic silicone lubricant, a stearate lubricant, an amide lubricant, and a fatty ester lubricant.

5. The method for preparing a brominated flame-retardant reinforced nylon material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The components except glass fiber are placed in a high-speed mixer for mixing according to proportion, and then transferred from the main feeding port to a twin-screw extruder. At the same time, glass fiber is added to the side feeding port for mixing and melt extrusion granulation to obtain the brominated flame retardant reinforced nylon material.

6. Use of the brominated flame retardant reinforced nylon material according to any one of claims 1 to 4 in the preparation of electronic and electrical products.

Citation Information

Patent Citations

  • Zirconium hydroxide

    CN101389570A

  • Coarse-grained sphere-like zirconium hydroxide with large specific surface area and preparation method of zirconium hydroxide

    CN105502490A

  • Flame-proof smoke-inhibiting nylon 6 composite material

    CN101250323A

  • Ultraviolet-aging-resistant and flame-retardant nylon composite material and preparation method thereof

    CN107446349A

  • Low-density low-odor bromine-based flame retardant reinforced nylon 66 and preparation method thereof

    CN109705571A

Cited By

  • XPS flame-retardant master batch and preparation method thereof

    CN119570076A

  • XPS flame retardant masterbatch and preparation method thereof

    CN119570076B